Pembelajaran Istima' Dengan Menggunakan Aplikasi Plotagon Story - Afifatun Nafsiyah; Faizah; Masyitoh; Laili Mas Ulliyah Hasan (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2025)
This study aims to develop and test the effectiveness of Arabic listening skills instructional media based on the Plotagon Story multimedia application for Grade IX students at Nahdhatul Athfal. The research was motivated by field findings indicating a lack of relevant instructional media aligned with textbook materials and low student comprehension in listening skills. The study employed the Research and Development (R&D) method using the Borg & Gall model, which includes needs analysis, product design, expert validation, product revision, limited trial, and field testing. Research instruments included observation, interviews, questionnaires, and tests. The results showed that the Plotagon Story application significantly improved students’ listening comprehension, as reflected in the increase in post-test scores and the high level of student satisfaction with the developed media. These findings support Vygotsky’s social constructivism approach, where learning becomes more effective through social interaction and the use of contextual media. Therefore, this media is recommended as an innovative alternative for communicative and participatory Arabic language learning.